ANTI-S100A4 MONOCLONAL ANTIBODY TREATMENT AMELIORATES SKIN FIBROSIS IN INFLAMMATORY AND NON-INFLAMMATORY PRE-CLINICAL MODELS OF SYSTEMIC SCLEROSIS - Tomcik, M.; Trinh, Minh Thuong; Trinh-Minh, T.; Tran Manh, Cuong; Storkanova, H.; Storkanova, L.; Senolt, L.; Klingelhofer, J.; Hussain, R. I.; Hallen, J.; Distler, Jörg (ANNALS OF THE RHEUMATIC DISEASES, 2021)
CRIS-Team WoS Importer:2021-10-01

Blocking IL-1, IL-33 and IL-36 Signaling with the Anti-IL1RAP Antibody mCAN10 Ameliorates Inflammation and Fibrosis in Preclinical Models of Systemic Sclerosis - Gronberg, Caitriona; Rattik, Sara; Kunz, Meik; Thoung Trinh-Minh,; Tran Manh, Cuong; Zhou, Xiang; Skoog, Petter; Liberg, David; Distler, Jörg (ARTHRITIS & RHEUMATOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-13

DEREGULATION OF TFAM EXPRESSION PROMOTES MITOCHONDRIAL DAMAGE AND FIBROBLAST ACTIVATION IN SYSTEMIC SCLEROSIS - Zhou, Xiang; Trinh, Minh Thuong; Tran Manh, Cuong; Giessl, A.; Bergmann, Christina; Györfi, Andrea-Hermina; Schett, Georg; Distler, Jörg (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

DYNAMIC CHANGES IN O-GLCNACYLATION REGULATE OSTEOCLAST DIFFERENTIATION AND BONE LOSS IN ARTHRITIS - Chen, Chih-Wei; Li, Y. N.; Trinh, Minh Thuong; Honglin, Z.; Matei, Alexandru-Emil; Ding, Xiao; Tran Manh, Cuong; Xu, Xiaohan; Liebel, C.; Liang, Ruifang; Huang, M. C.; Lin, N. Y.; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2021)
CRIS-Team WoS Importer:2021-10-01

Dynamic changes in O-GlcNAcylation regulate osteoclast differentiation and bone loss via nucleoporin 153 - Li, Yi-Nan; Chen, Chih-Wei; Trinh, Minh Thuong; Zhu, Honglin; Matei, Alexandru-Emil; Györfi, Andrea-Hermina; Kuwert, Frederic; Hubel, Philipp; Ding, Xiao; Tran Manh, Cuong; Xu, Xiaohan; Liebel, Christoph; et al. (Bone Research, 2022)
Bone mass is maintained by the balance between osteoclast-induced bone resorption and osteoblast-triggered bone formation. In inflammatory arthritis such as rheumatoid arthritis (RA), however, increased osteoclast differentiation and activity skew this balance resulting in progressive bone loss. O-GlcNAcylation is a posttranslational modification with attachment of a single O-linked β-D-N-acetylglucosamine (O-GlcNAc) residue to serine or threonine residues of target proteins. Although O-GlcNAcylation is one of the most common protein modifications, its role in bone homeostasis has not been systematically investigated. We demonstrate that dynamic changes in O-GlcNAcylation are required for osteoclastogenesis. Increased O-GlcNAcylation promotes osteoclast differentiation during the early stages, whereas its downregulation is required for osteoclast maturation. At the molecular level, O-GlcNAcylation affects several pathways including oxidative phosphorylation and cell-cell fusion. TNFα fosters the dynamic regulation of O-GlcNAcylation to promote osteoclastogenesis in inflammatory arthritis. Targeted pharmaceutical or genetic inhibition of O-GlcNAc transferase (OGT) or O-GlcNAcase (OGA) arrests osteoclast differentiation during early stages of differentiation and during later maturation, respectively, and ameliorates bone loss in experimental arthritis. Knockdown of NUP153, an O-GlcNAcylation target, has similar effects as OGT inhibition and inhibits osteoclastogenesis. These findings highlight an important role of O-GlcNAcylation in osteoclastogenesis and may offer the potential to therapeutically interfere with pathologic bone resorption.
CRIS-Team Scopus Importer:2022-08-05

Impaired Mitochondrial Transcription Factor A Expression Promotes Mitochondrial Damage to Drive Fibroblast Activation and Fibrosis in Systemic Sclerosis - Zhou, Xiang; Trinh, Minh Thuong; Tran Manh, Cuong; Gießl, Andreas; Bergmann, Christina; Györfi, Andrea-Hermina; Schett, Georg; Distler, Jörg (Arthritis and Rheumatology, 2022)
Objective Mitochondrial transcription factor A (TFAM) controls the transcription of core proteins required for mitochondrial homeostasis. This study was undertaken to investigate changes in TFAM expression in systemic sclerosis (SSc), to analyze mitochondrial function, and to evaluate the consequences for fibroblast activation. Methods TFAM expression was analyzed by immunofluorescence and Western blotting. The effects of TFAM knockout were investigated in cultured fibroblasts and in murine models of bleomycin-induced skin fibrosis, bleomycin-induced lung fibrosis, and skin fibrosis induced by overexpression of constitutively active transforming growth factor beta type I receptor (TGF beta R Iota). Results TFAM expression was down-regulated in fibroblasts in SSc skin and in cultured SSc fibroblasts. The down-regulation of TFAM was associated with decreased mitochondrial number and accumulation of damaged mitochondria with release of mitochondrial DNA (mtDNA), accumulation of deletions in mtDNA, metabolic alterations with impaired oxidative phosphorylation, and release of the mitokine GDF15. Normal fibroblasts subjected to long-term, but not acute, exposure to TGF beta mimicked SSc fibroblasts, with down-regulation of TFAM and accumulation of mitochondrial damage. Down-regulation of TFAM promoted fibroblast activation with up-regulation of fibrosis-relevant Gene Ontology terms in RNA-Seq, partially in a reactive oxygen species-dependent manner. Mice with fibroblast-specific knockout of Tfam were prone to fibrotic tissue remodeling, with fibrotic responses even to NaCl instillation and enhanced sensitivity to bleomycin injection and overexpression of constitutively active TGF beta RI. TFAM knockout fostered Smad3 signaling to promote fibroblast activation. Conclusion Alterations in the key mitochondrial transcription factor TFAM in response to prolonged activation of TGF beta and associated mitochondrial damage induce transcriptional programs that promote fibroblast-to-myofibroblast transition and drive tissue fibrosis.
CRIS-Team WoS Importer:2022-04-15

Targeting of canonical WNT signaling ameliorates experimental sclerodermatous chronic graft-versus-host disease - Zhang, Yun; Shen, Lichong; Dreißigacker, Katja; Zhu, Honglin; Trinh, Minh Thuong; Meng, Xianyi; Tran Manh, Cuong; Dees, Clara; Matei, Alexandru-Emil; Chen, Chih-Wei; Ditschkowski, Markus; Krauss, Stefan; et al. (Blood, 2021)
Chronic graft-versus-host disease (cGVHD) is a major life-threatening complication of allogeneic hematopoietic stem cell transplantation. The molecular mechanisms underlying cGVHD remain poorly understood, and targeted therapies for clinical use are not well established. Here, we examined the role of the canonical WNT pathway in sclerodermatous cGVHD (sclGVHD). WNT signaling was activated in human sclGVHD with increased nuclear accumulation of the transcription factor β-catenin and a WNT-biased gene expression signature in lesional skin. Treatment with the highly selective tankryase inhibitor G007-LK, the CK1α agonist pyrvinium, or the LRP6 inhibitor salinomycin abrogated the activation of WNT signaling and protected against experimental cGVHD, without a significant impact on graft-versus-leukemia effect (GVL). Treatment with G007-LK, pyrvinium, or salinomycin almost completely prevented the development of clinical and histological features in the B10.D2 (H-2d) → BALB/c (H-2d) and LP/J (H-2b) → C57BL/6 (H-2b) models of sclGVHD. Inhibition of canonical WNT signaling reduced the release of extracellular matrix from fibroblasts and reduced leukocyte influx, suggesting that WNT signaling stimulates fibrotic tissue remodeling by direct effects on fibroblasts and by indirect inflammation-dependent effects in sclGVHD. Our findings may have direct translational potential, because pyrvinium is in clinical use, and tankyrase inhibitors are in clinical trials for other indications.
CRIS-Team Scopus Importer:2021-05-28